BAYI TABUNG MENURUT DIMENSI HUKUM HINDU (PERSPEKTIF LONTAR BHUANA MAHBAH) - Harsananda, Hari; Adi Widnyana, I Made (Institut Hindu Dharma Negeri Denpasar, 2020)
Marriage is a phase that binds a couple called husband and wife in a marriage bond. The purpose of marriage one of course is to have offspring as a family successor. But not all couples can have offspring naturally due to interference with reproduction in one partner or both partners, so they are considered as unproductive couples. However, as advances in the health sector began to be found assisted reproductive technology methods, which allow unproductive couples to have offspring through the method of fertilization outside the womb, henceforth this program is often known as the IVF program. However, this program cannot be immediately accepted in the community, causing controversy in its journey.In this paper, the IVF method is seen from the perspective of the legality ofnational law and Hindu religious law, which method of IVF is something that can be done with its terms and conditions. In national law it is regulated that IVF is legal as long as the sperm and egg cells that will be fertilized through this program are from a legitimate married couple. Likewise Hindu teaching in lontar bhuana mahbah views this positively, because having offspring is a good thing and can help ancestors in terms of experiencing the process of reincarnation, but in the process of implementing IVF there are some formulations of the requirements that must be done by Hindu couples in undergoing a baby program This tube, which is a masturbation carried out in order to obtain offspring is not a masturbation aimed at achieving sexual satisfaction (masturbation) but purely for health, and if an abortion occurs, the fetus who died must receive a ceremony of panglungahan